2007
DOI: 10.1289/ehp.9504
|View full text |Cite
|
Sign up to set email alerts
|

Hair Manganese and Hyperactive Behaviors: Pilot Study of School-Age Children Exposed through Tap Water

Abstract: BackgroundNeurotoxic effects are known to occur with inhalation of manganese particulates, but very few data are available on exposure to Mn in water. We undertook a pilot study in a community in Québec (Canada) where naturally occurring high Mn levels were present in the public water system. Our objective was to test the hypothesis that greater exposure to Mn via drinking water would be reflected in higher Mn content in hair which, in turn, would be associated with increased level of hyperactive behaviors.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
240
6
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(261 citation statements)
references
References 30 publications
13
240
6
2
Order By: Relevance
“…High levels of Mn in drinking water in Canada have been found to lead to significantly higher levels of Mn in hair samples in school-age children. The increased hair Mn concentrations are significantly associated with increased hyperactive behaviors [49], impaired cognitive development [47], and a decrease in IQ points [50]. In Italy, school-age children living near a ferroalloy plant have been found to have significant impairment of motor coordination, hand dexterity, and odor identification after exposure to excess levels of Mn in soils [51].…”
Section: Absorption Distribution and Eliminationmentioning
confidence: 99%
“…High levels of Mn in drinking water in Canada have been found to lead to significantly higher levels of Mn in hair samples in school-age children. The increased hair Mn concentrations are significantly associated with increased hyperactive behaviors [49], impaired cognitive development [47], and a decrease in IQ points [50]. In Italy, school-age children living near a ferroalloy plant have been found to have significant impairment of motor coordination, hand dexterity, and odor identification after exposure to excess levels of Mn in soils [51].…”
Section: Absorption Distribution and Eliminationmentioning
confidence: 99%
“…39 A study in Quebec, Canada, showed a strong correlation between manganese concentrations in hair and hyperactivity. 40 School-aged children living near manganese mining and processing facilities have shown associations between airborne manganese concentrations and diminished intellectual function 41 and with impaired motor skills and reduced olfactory function. 42 These results are supported by experimental findings in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Data from rodent studies generally offer conflicting reports on how Mn exposure affects neurochemistry and motor function. A general consensus regarding the effects of Mn on motor function is that hyperactivity is observed early in Mn toxicity in the young or after low cumulative doses, in both human and animal studies (Bouchard et al, 2007; Nachtman et al, 1986), and as the disease progresses and cumulative dose levels increase, patients and animals both tend to become hypoactive (Oszlanczi et al, 2010; Torrente et al, 2005). …”
Section: Introductionmentioning
confidence: 99%